Quantitative Determination of Lidocaine Hydrochloride in Pharmaceutical Preparations Using HPLC-UV Detection - Khan, Nadeem Ul Hassan; Hamad, Asad; Quratulain,; Suleman, Naveed; Rashid, Sana; Abdul Sami,; Nawaz, Muhammad Aamir (Indus Journal of Bioscience Research, 2025)
Objective: To develop and validate a robust and sensitive High-Performance Liquid Chromatography (HPLC) method with ultraviolet (UV) detection for the quantification of Lidocaine-HCl in pharmaceutical formulations. Methods: An Ion Pac Ercus C18 reversed-phase column (250 mm × 4.5 mm, 5 µm) was used at 25°C with a mobile phase of water and acetonitrile (80:20, v/v) containing 5% acetic acid (pH 3.4). The flow rate was maintained at 1.0 mL/min, and detection was performed at 254 nm. Calibration standards (0.1–0.5 µg/mL) were prepared, and validation parameters including linearity, sensitivity, precision, and accuracy were assessed. Recovery studies were performed using spiked commercial samples. Results: The method showed excellent linearity (R² = 0.9987). LLOD and LLOQ were 0.00521 µg/mL and 0.01645 µg/mL, respectively. Intra- and inter-day precision had RSD values ≤0.57%. Recovery ranged from 96% to 100%. Retention time was consistent at 12.5 minutes. Conclusion: This validated HPLC-UV method is precise, sensitive, and reliable for routine quantification of Lidocaine-HCl, ensuring pharmaceutical quality control.